An Analysis of Delusion on Jake in I’m Thinking of Ending Things Film - Salmansyah, Fandy; Natsir, M.; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This research discusses the delusion of the character Jake, as seen in the film I'm Thinking of Ending Things. This study aims to identify the types of delusions and the causes of delusions by Jaimie Leeser and William O'Donohue. The theory of delusions is used to identify the types of delusions experienced by Jake and the causes of delusion in the film. This study also uses the theory of character and characterization by Dennis W. Petrie and Joseph M. Boggs to describe how the types and causes of delusions are depicted in the character Jake, who suffers delusions. This study uses qualitative methods as research methods. This study shows that there are three types of delusions experienced Jake’s character in the film. The delusions depicted in the film are erotomania where Jake believes he has a relationship; persecutory delusions when Jake feels someone is watching them make him harmed and angry, and grandiose delusions that he believed he had a unique ability and found something new in his world until he gets the Nobel medallion and everyone recognizes and appreciates him. The causes of delusions are also depicted in the film which is environmental causes such that Jake is portrayed as a lonely person and always bullied at school and genetic causes from Jake's father who has a history of Dementia which was passed down to Jake. Delusions in the film have an important role in the plot of the story to distinguish delusion and reality to make the audience understand what happened in this film.Key words: delusion, character, causes of delusion.